EFFECT OF PLAYING METHOD USING MEDIA MADE OF TEACHERS BASED ON ENVIRONMENT ABILITY TO CLASSIFICATE AND COUNTING (Experimental Study at TK NEGERI 3 South Bengkulu) - Masmidawati Masmidawati; Nina Kurniah (UNIB Press, 2018)
This study aims to describe the differences in the ability to classify and count between groups of children who use the assisted play method of environmentally based teacher-made media and groups of children who use the playing method with poster media at TK Negeri 3 Bengkulu Selatan. This study used an experimental method with a pretest-posttest control group design. Collecting data in this study using the observation sheet the ability to classify and the ability to count. The data analysis of this study used the t-test. The results showed that the method of playing assisted by environmentally based teacher-made media has a significant effect on the ability to classify and count. The method of playing using environmentally based teacher-made media that is done appropriately, effectively affects the ability to classify and count in the children of TK Negeri 3 Bengkulu Selatan. The implication of this research is that the teacher applies classifying and arithmetic learning in early childhood not limited to media commonly used in the classroom but can also use environmentally based teacher-made media. The results of this study recommend that the environmentally-based teacher-assisted media-assisted play method can improve classifying and counting skills